Determination of the parton distribution functions of the proton from ATLAS measurements of differential W± and Z boson production in association with jets - Fiolhais, M. C. N. (2021)
This article presents a new set of proton parton distribution functions, ATLASepWZVjet20, produced in an analysis at next-to-next-to-leading order in QCD. The new data sets considered are the measurements of W + and W− boson and Z boson production in association with jets in pp collisions at p s = 8TeV performed by the ATLAS experiment at the LHC with integrated luminosities of 20.2 fb−1 and 19.9 fb−1, respectively. The analysis also considers the ATLAS measurements of differential W± and Z boson production at p s = 7TeV with an integrated luminosity of 4.6 fb−1 and deep-inelastic-scattering data from e±p collisions at the HERA accelerator. An improved determination of the sea-quark densities at high Bjorken x is shown, while confirming a strange-quark density similar in size to the up- and down-sea-quark densities in the range x . 0.02 found by previous ATLAS analyses.